Titanium nanotubes modulate immunophenotyping and cytokine secretion of T cells via IL-17A: a bioinformatic analysis and experimental validation - Jingju Yin; Jingju Yin; Jingju Yin; Jingju Yin; Yunyang Liao; Yunyang Liao; Yunyang Liao; Yunyang Liao; Shaofeng Liu; Shaofeng Liu; Shaofeng Liu; Shaofeng Liu; et al. (Frontiers in Immunology)
ObjectWe aim to explore the immunomodulatory properties of T cells on different titanium nanotubes and the key immunological factors involved in this process.MethodsTranscriptome data from GEO database of healthy people and healthy implants were used to analyze cell infiltration and factor distribution of adaptive immune using bioinformatics tools. T cells from activated rat were cultured on titanium nanotubes that were prepared by anodization with different diameters (P-0, NT15-30 nm, NT40-100 nm, NT70-200 nm). The proliferation and expressions of the main transcription factors and cytokines of T-cells were detected. Magnetic bead sorting of CD3+ T cells and transcriptome sequencing were performed to explore the signaling pathways and key immune factors that may influence the related immune responses.ResultsBioinformatics analysis showed that healthy peri-implant tissues were enriched by the most of T-cell subtypes. T-cell-mediated adaptive immunological responses involved IL-17A. On the third day, the NT15 and NT40 groups showed significantly higher pro-proliferative effects than the NT70 group (P<0.05). Notably, the NT40 group exhibited the lowest T-bet expression (P<0.05) along with the highest levels of Rorγt, Gata3, and Foxp3(P<0.05), followed by the NT15 group. Additionally, the NT40 group demonstrated reduced RANKL, TNF-α, and IL-6 (P<0.05) and increased OPG and IL-10 (P<0.05). Meanwhile, the NT15 group had lower IFN-γ expression(P>0.05) but higher IL-4, and TGF-β1 expressions(P<0.05). Differential expressed genes (DGEs) of T-cell related to the morphologies of titanium nanotubes were mostly enriched in the IL-17 signaling pathway mediated by IL-17A/F. Gene and protein expressions indicated that the NT40 group had the highest secretion in IL-17A of T cells.ConclusionTitanium nanotube morphologies in medium (100 nm) and small (30 nm) sizes significantly influence T cell differentiation and immune factor secretion, with T-cell-derived IL-17A likely playing a key regulatory role.